Ciclagem biogeoquímica dos nutrientes em um povoamento do híbrido Eucalyptus urophylla x E. sp. submetido a exclusão parcial da precipitação interna - Poleto, Gian Carlos (2019)
The hybrid Eucalyptus urophylla S.T. Blake is one of the most productive clones grown in Brazil. Although mineral fertilization through chemical fertilization is a silvicultural operation that generates good productivity results, there are other forms of nutrient entry, among them, the atmospheric deposition and the decomposition of the organic matter present in the soil. The objective of this study was to evaluate the biogeochemical nutrient cycling in a Eucalyptus urophylla x E. sp., subject to partial exclusion of throughfall, in Telêmaco Borba, PR. For that, two experimental treatments were established: one with 100% of the internal precipitation (SE), and the other with 70% of the internal precipitation (CE). In order to quantify the throughfall, three collectors were installed per treatment, which were distributed in three different positions, being: in the line, in the line and in the diagonal of four trees. Three sets of flow collectors were also installed by trunk per treatment. The litterfall was estimated through the installation of nine collectors per treatment, also in different positions, in the line, between line and diagonal between four trees. For the evaluation of accumulated litter, 30 random samples were collected in each treatment. The material was separated into three fractions (leaves, branches and miscellaneous). For the determination of biomass and fine root density, 36 soil samples were collected per treatment at depths of 0-10 cm; 10-20 cm; 20-30 cm; 30-40 cm; 40-50 cm and 50-60 cm along the soil profile. For the determination of above-ground biomass, nine trees were sampled per treatment, sectioned at ground level and fractionated in wood, bark, live branch, dead branch and leaves. The annual rainfall was 1.627,25 mm, with 12.29% and 17.18% being intercepted by the crown of the trees in the treatment CE and SE partial exclusion, respectively. The input of nutrients by rainfall was 44.01 kg ha-1. In the treatment SE, the internal precipitation and the stemflow presented a nutrient intake of 46.9 kg ha-1 and 3.11 kg ha-1, respectively. In the treatment CE partial of the internal precipitation, a contribution of 28.61 kg ha-1 occurred in the internal precipitation and 2.87 kg ha-1 in stemflow. The interaction of rainfall with canopy enriches rainfall with nutrients in both treatments. The annual amount of litter produced was 6991.40 kg ha-1 in treatment CE and 8168.73 kg ha-1 in treatment SE. The total accumulated litter on the soil was 16.288,91 kg ha-1 for treatment CE and 18081.60 kg ha-1 for treatment SE. The fine root biomass in the treatment CE presented 2930.55 kg ha-1 and 1726.05 kg ha-1 in the treatment SE. The mean fine root density of the treatment CE resulted in 0.44 cm cm³, being 54.55% higher than the treatment SE (0.20 cm cm³). The total biomass above the soil was 208.26 Mg ha-1 in treatment CE and 221.00 Mg ha-1 for the treatment SE, with decreasing sequence of allocation in wood > bark > live branches > leaves > dead branch in both treatments.